2013
DOI: 10.1016/j.neuron.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A Cortico-Hippocampal Learning Rule Shapes Inhibitory Microcircuit Activity to Enhance Hippocampal Information Flow

Abstract: Summary How does coordinated activity between distinct brain regions implement a set of learning rules to sculpt information processing in a given neural circuit? Using interneuron cell-type specific optical activation and pharmacogenetic silencing in vitro, we show that temporally precise pairing of direct entorhinal perforant path (PP) and trisynaptic Schaffer collateral (SC) inputs to CA1 pyramidal cells selectively suppresses SC-associated perisomatic inhibition from cholecystokinin (CCK) expressing intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
165
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(182 citation statements)
references
References 58 publications
(93 reference statements)
13
165
1
Order By: Relevance
“…During the recall phase (center arm) of the T maze task, the CA3 and EC3 inputs may cooperatively increase their influence on CA1 (Montgomery and Buzsáki, 2007; Yamamoto et al, 2014). Properly timed CA3 and EC3 input can also become more effective through suppression of feed-forward inhibition (Buzsáki et al, 1995; Yeckel and Berger, 1990; Leão et al, 2012; Basu et al, 2013) or facilitating mechanisms that can overcome inhibition (Remondes and Schuman, 2002; Jarsky et al, 2005; Takahashi and Magee, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…During the recall phase (center arm) of the T maze task, the CA3 and EC3 inputs may cooperatively increase their influence on CA1 (Montgomery and Buzsáki, 2007; Yamamoto et al, 2014). Properly timed CA3 and EC3 input can also become more effective through suppression of feed-forward inhibition (Buzsáki et al, 1995; Yeckel and Berger, 1990; Leão et al, 2012; Basu et al, 2013) or facilitating mechanisms that can overcome inhibition (Remondes and Schuman, 2002; Jarsky et al, 2005; Takahashi and Magee, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Feed-forward inhibition thus can reduce the spike responses of principal neurons, by competing with dendritic excitation or reducing output spiking. A recent study suggested that cholecystokinin (CCK) positive basket cells are primarily involved in the feed-forward inhibition of hippocampal CA1 pyramidal cells (Basu et al , 2013). Whether feed-forward inhibition brings about a subtractive or divisive action in the visual cortex is still debated (Atallah et al , 2012; Lee et al , 2012; Wilson et al , 2012; Lee et al , 2014a) and may depend whether the inhibitory target is dendrites or the perisomatic region.…”
Section: Inhibitory Control In Circuitsmentioning
confidence: 99%
“…In the hippocampus, a subset of cholecystokinin (CCK) positive interneurons in CA1 is recruited by Schaffer collaterals and provide feedforward inhibition to control the coincident excitation of CA1 pyramidal neurons by convergent entorhinal perforant path (PP) and SC inputs. The temporally precise pairing of PP and SC inputs suppresses SC-associated CCK interneurons and provide a hetero-synaptic learning rule for gating information flow through hippocampal circuits (Basu et al, 2013). Together, these studies begin to provide compelling evidence that phenotypically diverse interneurons do not reflect a continuum with no definable class boundary and distinct function (Petilla Interneuron Nomenclature et al, 2008).…”
Section: Genetic Targeting Of Gabaergic Interneurons and Progenitorsmentioning
confidence: 99%